The Relationship of Workload with the Quality of Nursing Services in Hemodialysis Installations - Tri Ratnanningsih; Faisal Ibnu; M.Maridi; Seriga Banjarnahor (Window of Health : Jurnal Kesehatan, 2024)
The quality of nursing services for hemodialysis patients is determined by the role and performance of nurses. High workloads are often the reason nurses leave work, which can disrupt the continuity of patient care. A high workload can have a negative impact on the quality of nurses' work, while a balanced workload can improve the quality of work. This study used a cross-section design with a sample of 35 hemodialysis nurses at RSUD Dr. Soetomo. The research was carried out in the Hemodialysis room at Dr Soetomo Hospital, Surabaya. Research data regarding workload and service quality variables was collected through questionnaires. Research data was processed using Spearmen rho with a p-value ≤ 0.05. The statistical test results show that the p-value is 0.000, so it can be interpreted that H0 is rejected. This indicates a relationship between nurses' workload and the quality of hemodialysis services. The workload creates optimal nurse performance in carrying out actions. The performance of nurses in hemodialysis tasks, which are quite complex, with the number of patients being disproportionate to the number of nurses, has an effect on the quality of nursing services.